Faraq dalam Pernikahan Sindiket di Johor Malaysia dan Relevansinya dengan Penanganan Nikah Sirri di Indonesia - Khairani Khairani (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2014)
Marriage sindiket almost similar meaning with marriage Sirri Indonesia. Johor Malaysia wedding sindiket has caused a lot of problems in the community, especially about the validity of his marriage. Faraq or annulment of marriage is a way for the completion of a dubious marriage. so immoral that occur from dubious marriage not continues. Faraq mechanism in this sindiket marriage has been defined in Enakmen 17 of 2003 Islamic Family Law. Court that decides whether the marriage can be forwarded or difaraq sindiket. The factors that led to a marriage should sindiket difaraq partly because the elements of the pillars of marriage are not met. Faraq provisions in this sindiket marriage should be able to consider in preventing and addressing issues arising from the consequences of marriage Sirri in Indonesia. Kata kunci: faraq, pernikahan sindiket, nikah siri